2022
DOI: 10.2147/ott.s329262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Transglutaminase in Patients with Glioblastoma: Current Perspectives

Abstract: Tissue transglutaminase (tTG) is a rather unique GTP-binding/protein crosslinking enzyme that has been shown to play important roles in a number of cellular processes that impact both normal physiology and disease states. This is especially the case in the context of aggressive brain tumors, such as glioblastoma. The diverse roles played by tTG in cancer survival and progression have led to significant interest in recent years in using tTG as a therapeutic target. In this review, we provide a brief overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…GTP closes tG, and in this state, tG acts as a GTPase (Liu et al, 2002;Pinkas et al, 2007). The increased expression of tG is linked to several different cancers (Mann et al, 2006;Katt et al, 2022). Interestingly, when tG is mutated to stay in an open conformation, it is toxic to cells (Datta et al, 2007;Katt et al, 2018) for reasons that are poorly understood.…”
Section: Comparing Diffusive and Chaotic Advection Mixingmentioning
confidence: 99%
“…GTP closes tG, and in this state, tG acts as a GTPase (Liu et al, 2002;Pinkas et al, 2007). The increased expression of tG is linked to several different cancers (Mann et al, 2006;Katt et al, 2022). Interestingly, when tG is mutated to stay in an open conformation, it is toxic to cells (Datta et al, 2007;Katt et al, 2018) for reasons that are poorly understood.…”
Section: Comparing Diffusive and Chaotic Advection Mixingmentioning
confidence: 99%
“…In the BTB, BMECs display some features that are typical of the primary tumor and that differentiate these cells from healthy BMECs [41][42][43] (Figure 1). First, BMECs present a flat appearance with large nuclei, abundant cytoplasm, multiple nucleoli and veil-like structures [44,45], losing their canonical cobblestone-like appearance [37].…”
Section: Characteristics Of Gbm-associated Bmecsmentioning
confidence: 99%
“…SAXS can also be used to measure protein conformational changes that are associated with disease states and has the potential to screen conformational state inhibitors that are able to trap a protein target in a desired conformation. Many proteins exist in multiple conformations, dependent on the environmental conditions or ligand binding, and this has previously been shown to play an important role in several diseases, including Alzheimer’s disease and liver disease. , For example, the enzyme tissue transglutaminase (tTG) is frequently overexpressed in cancer and has been implicated in a number of diseases, including celiac disease and neurodegenerative disorders. tTG can adopt two strikingly distinct conformations designated as open- and closed-state conformations that are regulated by calcium and guanine nucleotide binding, respectively. , The transitions between these two conformational states involve large-scale rearrangements of the C-terminal beta barrels, resulting in a displacement of greater than 100 Å. Previous studies have shown that nucleotide binding-defective mutants, which can only adopt the open state, are cytotoxic to cancer cells that overexpress tTG. This finding led to the development of conformational state inhibitors of the enzyme, which are able to trap tTG in an open state conformation and have been effective in killing cancer cells .…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 99%